(untitled) (Revista Iberoamericana de Bioética, 2023)
Respect for the principle of autonomy in pediatrics entails a double challenge: on the one hand, incorporating parents into decision-making, and, on the other, proportionally and progressively incorporating the minor himself/herself. Despite the legal and ethical development of the mature minor doctrine, there is little evidence of it being carried out in routine clinical practice. One of the difficulties is that, for decades, the discussion on the maturity and competence of minors in health decision-making has focused more frequently on regulatory and legal aspects than on evidence and clinical practice. Understanding autonomy from a relational aspect makes it possible for pediatrics to incorporate factors linked to development and the maturation process, as well as involve sociocultural, family, personal, psychobiographical, and learning factors. This sphere of relational autonomy gives rise to a shared decision-making model.